Service-Oriented Computing - ICSOC 2014 Workshops : WESOA; SeMaPS, RMSOC, KASA, ISC, FOR-MOVES, CCSA and Satellite Events, Paris, France, November 3-6, 2014, Revised Selected Papers - Toumani, Farouk; Pernici, Barbara; Grigori, Daniela; Benslimane, Djamal; Mendling, Jan.; Ben Hadj-Alouane, Nejib; Blake, Brian; Perrin, Olivier; Saleh Moustafa, Iman.; Bhiri, Sami.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the revised selected papers of the 12th International Conference on Service-Oriented Computingm, ICSOC 2015, held in Paris, France, in November 2014. The conference hosted the following seven workshops: 10th International Workshop in Engineering Service-Oriented Applications, WESOA 2014; First Workshop on Resource Management in Service-Oriented Computing, RMSOC 2014; First International Workshop on Knowledge Aware Service Oriented Applications, Performance Assessment and Auditing in Service Computing, KASA 2014; Workshop on Intelligent Service Clouds, ISC 2014; Third International Workshop on Self-Managing Pervasive Service Systems, SeMaPS 2014; First International Workshop on Formal Modeling and Verification of Service-Based Systems, FOR-MOVES 2014; 4th International Workshop on Cloud Computing and Scientific Applications, CCSA 2014. The papers included in this volume were carefully reviewed and selected from numerous submissions. They address various topics in the service-oriented computing domain and its emerging applications. enUsed="false" QFormat="true" Name="Intense Reference"/>.
Engineering service-oriented applications -- Resource management in service-oriented computing -- Knowledge aware service oriented applications -- Intelligent service clouds -- Self-managing pervasive service systems -- Formal modeling and verification of service-based systems -- Cloud Computing and scienfific applications -- PhD symposium track -- Demo track.
Keywords: Software engineering; Information technology; Information systems; Information Systems; Computer science; Software Engineering; Information Systems Applications (incl. Internet).; IT in Business; Computer Appl. in Administrative Data Processing; Management of Computing and Information Systems; Computers and Society